PERANCANGAN MESIN PRESS BATAKO - , NIZAM JEFRY ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the competitive world of medium industry, the industry is expected to produce quickly and efficiently in order to achieve the production target. One taken to increase the production is to transform manual processes into mechanical processes. Because application of the system mechanical, can reduce the cost of production and ease the workload. The application of mechanical system on brick machine among others, handle or lever, energy potensial and centrifugal force. Implementation of the mechanical system can be simplify make of brick than manual process. The result of design brick machine can be ease and increase the capacity of brick production, because itâs able to produce 10 bricks on one of press. So this machine can help to ease making brick process.